Enhanced Photoluminescence Emission and Thermal Stability from Introduced Cation Disorder in Phosphors - Lin, Chun Che; Tsai, Yi-Ting; Johnston, Hannah E; Fang, Mu-Huai; Yu, Fengjiao; Zhou, Wuzong; Whitfield, Pamela; Li, Ye; Wang, Jing; Liu, Ru-Shi; Attfield, J Paul (Journal of the American Chemical Society, 2017)
Optimizing properties of phosphors for use in white-light-emitting diodes (WLEDs) is an important materials challenge. Most phosphors have a low level of lattice disorder due to mismatch between the host and activator cations. Here we show that deliberate introduction of high levels of cation disorder leads to significant improvements in quantum efficiency, stability to thermal quenching, and emission lifetime in Sr (Ca Ba ) Si N :Eu (x = 0-1.5) phosphors. Replacing Sr by a (Ca Ba ) mixture with the same average radius increases cation size variance, resulting in photoluminescence emission increases of 20-26% for the x = 1.5 sample relative to the x = 0 parent across the 25-200 °C range that spans WLED working temperatures. Cation disorder suppresses nonradiative processes through disruption of lattice vibrations and creates deep traps that release electrons to compensate for thermal quenching. Introduction of high levels of cation disorder may thus be a very useful general approach for improving the efficiency of luminescent materials.